(untitled) (Pedagogy of Higher and Secondary Education, 2022)
The article deals with the problems of psychological and medical-pedagogical guidance of teaching process at Technical Universities. It has been determined that the increase in duration and tenseness educational and informational load results in certain damage to the students protective system.